The market for corporate control and firm information environment: Evidence from five decades of data - Ni, Xiaoran; Wang, Ye; Yin, David (Journal of Banking & Finance, 2025)
This paper reconciles conflicting empirical findings in the takeover and firm transparency literature by utilizing a comprehensive takeover index from Cain, McKeon, and Solomon (2017). Examining a broad sample of U.S. public firms from 1970 to 2020, we document a negative relation between takeover susceptibility and firm opacity, measured primarily through stock price crash risk, and also through accrual/real earnings management, financial statement readability, analyst forecast dispersion, and voluntary disclosure. Stronger takeover threats mitigate crash risk by curtailing managerial empire-building incentives, promoting timely information disclosure, and constraining manipulative accounting practices. Our research confirms the effectiveness of the market for corporate control in addressing information-related agency problems and enhancing firm transparency. These findings persist across a broad range of firms and an extended time period, addressing the limitations of earlier studies. By employing a more holistic measure of takeover vulnerability and examining multiple facets of transparency, we provide a nuanced understanding of how corporate governance mechanisms influence firm performance and risk.